Apelin and Cardiovascular System - Yalcin, Mihriban (Current Overview on Disease and Health Research Vol. 11, 2023)
The purpose of the current study was to determine effects of apelin on the cardiovascular system in the light of the literature. Adipose tissue, which is considered as the body's energy store, makes important contributions to the functions of the organism through the many adipokines it produces. Apelin, one of this; is involved in the regulation of many processes such as primarily cardiovascular functions, fluid metabolism, response to stress via the hypothalamo-pituitary-adrenal axis, regulation of food intake via hypothalamic neuronal nuclei, energy metabolism and immune functions. Since the sequence of 13 amino acids in the structure of apelin is unchanged in all its forms, the basic structure of apelin is considered to be apelin-13.